The importance of approach the birth plan during prenatal care in basic health units Amazon - Mara Cristiany Rodrigues Spinola; Andressa Silva Oliveira; Thainá Jeanny Santos Marciel; Thayla Pantoja Campos Figueira; Luana Almeida dos Santos (Población y Salud en Mesoamérica)
Introduction: The Birth Plan (BP) is a document prepared by the pregnant Woman tongether with the professional who is accompanying her in her pregnancy process, Where you can list your choices regarding childbirth and first care for the newborn, providing her with the leading role and effective participation in all decisions regarding her pregnancy Objective:Report the importance of approaching the Birth Plan in basic units during prenatal care. Material and Methods: This is a field research with a qualitative approach, developed in 3 basic health units in the municipality of Santarem, inthe state of Pará. Results and discussions: During the interviews with the professionals, it was evident that although the nurses recognized the importance of the PP, the low adherence to the document is due to the professionals' lack of knowledge about it, as well as the lack of support from the municipal management and maternity hospitals in the continuity of care for this pregnant woman.Conclusion: The birth plan is an extremely important tool, but little used or commented on by the professionals who work directly in the program. Thus, there is an undeniable need for greater encouragement from professionals to adhere to this tool and for there to be effective support from maternity hospitals and from the municipal management itself, so that it is effective and continuity is given to the assistance to these pregnant women and, in this way, that they have their rights guaranteed and live a positive experience in relation to childbirth.